High-caloric food supplements in the treatment of amyotrophic lateral sclerosis: A prospective interventional study. Issue 7 (December 2013) - Dorst, Johannes; Cypionka, Joschka; Ludolph, Albert C.
Abstract: Weight loss is an independent prognostic factor in amyotrophic lateral sclerosis (ALS). We investigated whether the body weight of ALS patients who previously lost weight can be stabilized by a high-caloric diet. For this purpose we compared two different high-caloric food supplements: one with high fat content and one with high carbohydrate content. Twenty-six patients were randomly allocated to one of the therapeutic groups. Body weight, ALS functional rating scale-revised (ALSFRS-R), static vital capacity (SVC), bioelectrical impedance analysis (BIA), metabolic serum parameters, and adverse events were investigated. Results showed that body weight of ALS patients could be stabilized in both therapeutic groups after 12 weeks of therapy ( p = 0.008). The effect was greater in the group with high fat supplement though not statistically significant ( p = 0.37). In conclusion, high-caloric food supplements with high fat as well as high carbohydrate content are both suitable to stabilize the body weight of ALS patients. The effect of a high fat diet might be more pronounced. Since body weight is an independent prognostic factor in ALS it is possible that a high-caloric food supplement improves survival in ALS. However, this hypothesis can only be tested by conducting a placebo-controlled double-blinded trial of sufficient power.